University–School Partnerships in English Pre-service Teacher Education: A Dialogic Inquiry into a Co-teaching Initiative. Issue 3 (3rd July 2017) - Diamond, Fleur; Parr, Graham; Bulfin, Scott
Abstract: Evidence has been accumulating for some time about the impact of standards-based education reforms on schools and schooling, but there has been little research investigating the influence of these reforms on university-based initial teacher education (ITE). This article critically inquiries into the effects of these reforms on an ITE co-teaching project where a secondary English teacher in a school was seconded to work for a year as a teacher educator in an Australian university in a praxis-based partnership. Using Cavarero's framing of 'who' and 'what' narratives, and Bakhtinian discourse theory, the authors present three autobiographical narratives exploring different perspectives on their experiences in the co-teaching partnership. The article affirms the value of school–university praxis partnerships for speaking back to standards-based reforms, but acknowledges that this speaking back involves complex relational and dialogic work in grappling with institutional and system-wide policies and practices.